If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 + 3(4q + -2) = -15 + 10q + -18 Reorder the terms: 13 + 3(-2 + 4q) = -15 + 10q + -18 13 + (-2 * 3 + 4q * 3) = -15 + 10q + -18 13 + (-6 + 12q) = -15 + 10q + -18 Combine like terms: 13 + -6 = 7 7 + 12q = -15 + 10q + -18 Reorder the terms: 7 + 12q = -15 + -18 + 10q Combine like terms: -15 + -18 = -33 7 + 12q = -33 + 10q Solving 7 + 12q = -33 + 10q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-10q' to each side of the equation. 7 + 12q + -10q = -33 + 10q + -10q Combine like terms: 12q + -10q = 2q 7 + 2q = -33 + 10q + -10q Combine like terms: 10q + -10q = 0 7 + 2q = -33 + 0 7 + 2q = -33 Add '-7' to each side of the equation. 7 + -7 + 2q = -33 + -7 Combine like terms: 7 + -7 = 0 0 + 2q = -33 + -7 2q = -33 + -7 Combine like terms: -33 + -7 = -40 2q = -40 Divide each side by '2'. q = -20 Simplifying q = -20
| -5(6x-2)+2=-30x+12 | | -19g=2(-11g+16)-8 | | -20+2(-20t-20)=3(-16t+20) | | 103x+47=1283 | | 2u-2=-4 | | 2j-2j+8j-2j=72 | | 8x^4-14x^3-69x^2-14x+8=0 | | 56p+18p+4p-11p-66p=61 | | -10+-30+28=-16-16 | | 8u=12r | | P=-6(5-1) | | -75x+74x+2=-32 | | 6x+164=13x-11 | | 89n-27n-60n-71=-9 | | -10+-30+28=16-16 | | 16g+92g-76g-30g-96g=-94 | | -45=x-5y | | 7x-5+x=4x | | 27n+13n+23n-59n=100 | | 10u-3u-6u=30 | | 7x+5=10+3x | | -30c+32c-14=62 | | 26h+40h-24h-25h-10h+9=-47 | | 4x^2-62=98-6x^2 | | 16x-[8-3(9x-4)]=195 | | 50n-47n+39=-30 | | 16x-27=37 | | x-3=5.7 | | 8g+3=4g-10 | | 4n-15=101 | | 394-h=232 | | 5(3n+3n)=2(5n-4)6n |